Pengembangan LKPD Elektronik Berbasis Masalah Terintegrasi Potensi Lokal TPST Piyungan pada Materi Perubahan Lingkungan untuk Meningkatkan Kemampuan Pemecahan Masalah dan Literasi Lingkungan Peserta Didik Kelas X SMA - Lenny Yunitasari; Anggi Tias Pratama (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the characteristics and produce problem-based electronic student worksheets that are integrated with the local potential of TPST Piyungan in appropriate, practical, and effective environmental change material to improve students' problem-solving abilities and environmental literacy. This research is research and development (R&D) using the 4D model (Define, Design, Develop, and Disseminate). A field trial of electronic worksheets was carried out through quasi-experimental research with a pretest-posttest control group design. The field trial subjects were 72 students from two classes. Data analysis was carried out using the MANOVA test to analyze differences in students' problem-solving abilities and environmental literacy. The results of the research show that based on the assessment of expert lecturers, the content of electronic worksheets is very suitable for encouraging problem-solving abilities and environmental literacy, and the MANOVA test results show that there are differences in problem-solving ability and environmental literacy when using electronic worksheets based on problems integrated with the local potential of TPST Piyungan. It can be concluded that the integrated worksheet based on local potential problems at TPST Piyungan is feasible, practical, and effective for use in implementing environmental change materials